Evaluasi Program Pembelajaran Tematik Di MI Mitra PGMI STAIN Ponorogo - Fu'adi, Athok (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2014)
The purpose of this research is to evaluate thematic learning in Islamic School that becomes partner of PGMI (Education of Islamic Elementary School Teachers) that includes: 1) teachers’ context in thematic learning, 2) implementation of thematic learning, 3) supporting and inhibiting factorsof thematic learning.This research is a qualitative research and the subject of research is teacher in the lower class. The research instrument in this research is the researcher itself. The data is collected through conducting interview, observation,and documentation. Data validation is collected through conducting triangulation and observation continuously. Data analysis is done since collected data using interactive model that consist of three steps, such as data reduction, input data, and make conclusion.The result of this research shows that the teachers’ context in thematic learning for beginner class is already appropriate, whereas for their teaching experience is still less. However, from the result of training, it can be concluded that teachers actually could implement thematic learning well. The implementation of thematic learning is already good; it can be seen from the existence of lesson plans, display of students’ tasks, and also portfolioassessment which includes a lot of students’ practices and discussions. The supporting and inhibiting factors in the thematic learning is resulted from the teachers, the students, and the environment but those factors could besolved and fially the result is the thematic learning could be done well.Keywords: Evaluation, thematic learning